Closure of Emergency Intestinal Stoma in the Same Hospital Stay - AHMED MAHMOUD EL-HARRAZIN, SYED HAROON MANSOOR (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To assess the effectiveness of early stoma closure in terms of complications and hospital stay during management of initial operation. Background: Construction of a temporary intestinal stoma is a common pediatric surgical problem. They are associated with complications which are difficult to control. These temporary stomas need to be closed as soon as possible. Material and methods: Fifty children of different age groups, in which temporary stoma was constructed for various pathological conditions were studied to assess the results of early stoma closure in terms of complications as well as the duration of hospital stay. Seven (14%) patients were neonates of intestinal obstruction, 9(18%) had typhoid perforations whereas 34 (68%) presented with gut perforation due to trauma. Colostomy was made in 60% patients of which 90% were loop and 10% were divided colostomies. In rest of the 40% patients ileostomy was done of which 20% were divided and 80% were loop ileostomies. The average time between stoma formation and closure was 12.84 ± 1.82 days, with minimum and maximum days as 10 days and 16 days respectively. The mean hospital stay was 24.46±3.51 days with minimum and maximum hospital stay as 15 and 36 days respectively. Four (8%) patients developed abdominal distension, wound infection occurred in 7 (14%) , anastomotic leak, enterocutaneous fistula and adhesion-obstruction developed in 1(2%) patient each. Early closure of temporary stoma created during the initial operation can safely be done in the same hospital stay.